2006
DOI: 10.1001/archinte.166.3.285
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Low-Carbohydrate vs Low-Fat Diets on Weight Loss and Cardiovascular Risk Factors

Abstract: Background: Low-carbohydrate diets have become increasingly popular for weight loss. However, evidence from individual trials about benefits and risks of these diets to achieve weight loss and modify cardiovascular risk factors is preliminary. Methods: We used the Cochrane Collaboration search strategy to identify trials comparing the effects of lowcarbohydrate diets without restriction of energy intake vs low-fat diets in individuals with a body mass index (calculated as weight in kilograms divided by the squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

39
544
5
28

Year Published

2006
2006
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 862 publications
(616 citation statements)
references
References 29 publications
39
544
5
28
Order By: Relevance
“…Both low-fat highcarbohydrate diets and low-carbohydrate high-fat diets have been found to be effective strategies for weight loss in intervention studies. [43][44][45][46] In our study, when carbohydrate intake was analysed in the same regression models as used for GL, no association with weight and waist circumference change was observed. Also noteworthy, the correlation coefficient between GL and carbohydrates was 0.98, whereas it was only 0.36 between GL and GI (data not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Both low-fat highcarbohydrate diets and low-carbohydrate high-fat diets have been found to be effective strategies for weight loss in intervention studies. [43][44][45][46] In our study, when carbohydrate intake was analysed in the same regression models as used for GL, no association with weight and waist circumference change was observed. Also noteworthy, the correlation coefficient between GL and carbohydrates was 0.98, whereas it was only 0.36 between GL and GI (data not shown).…”
Section: Discussioncontrasting
confidence: 52%
“…Ramadan fasting is a natural experiment that occurs annually for 1 month and requires specific practices, such as nocturnal consumption of food and changes in meal frequency, food quality, energy intake and sleep cycle. Different studies have reported both positive and negative effects (2003) Kassab (2003) Rahman (2004) Kassab (2004) Yucel ( Kassab (2003) Rahman (2004) Kassab (2004) Aksungar (2005) Lamine (2006) Mansi (2007) Haghdoost ( Weight loss may reduce cardiovascular morbidity and mortality and may lead to prevention of type 2 diabetes and improved control of hypertension (48)(49)(50) . At any given Husain (1987) El Ati (1995) Finch (1998) Adlouni (1998) Maislos (1998) Roky (2001) Kassab (2003) Rahman (2004) Kassab (2004) Aksungar (2005) Lamine (2006) Mansi (2007) Haghdoost ( The pooled or 'combined' mean difference was calculated by a fixed-effects model.…”
Section: Discussionmentioning
confidence: 99%
“…Fall in HDL-C is usual with a low-fat diet, around or less than 30% of energy. 40,41 It seems, therefore, that LC n-3 PUFAs in combination with highquality fish proteins could be an additional means to decrease cardiovascular risk during weight loss using diets with relatively low fat content.…”
Section: Discussionmentioning
confidence: 99%